Arah Baru Pengembangan Pendidikan Agama Islam di Sekolah: Telaah Kurikulum dan Model Pembelajaran - Rifa’i; Novitasri (STID Raudlatul Iman Sumenep, 2026)
In schools, Islamic Religious Education (PAI) encounters significant obstacles in addressing the modern era, including the secularization of values that causes changes in students' moral compass, the effects of digitization, and character crises. In addressing the needs of 21st-century education, PA learning, which is still the norm and less contextual, is deemed to be ineffective. The goal of this research is to investigate novel strategies for creating the PAI curriculum and learning models that integrate Islamic principles with current issues. This is a literature review that takes a conceptual approach, using critical analysis of Islamic education theories, national curriculum materials, and academic literature. The findings emphasize the necessity of a more inclusive and value-oriented PAI curriculum design that places emphasis on religious moderation, tolerance, and character development. Furthermore, in order for pupils to successfully incorporate Islamic principles into their everyday lives, PAI instruction should use active, cooperative, and practical approaches. As a result, the future advancement of PAI must incorporate Islamic principles, twenty-first-century needs, and pedagogical techniques that foster the complete development of students' personalities. Pendidikan Agama Islam (PAI) di sekolah menghadapi tantangan serius di era modern, seperti krisis karakter, digitalisasi, dan pengaruh nilai-nilai sekuler yang melemahkan moral siswa. Pembelajaran PAI yang bersifat normatif dan kurang kontekstual dianggap belum efektif menjawab tuntutan pendidikan abad ke-21. Penelitian ini bertujuan mengeksplorasi arah baru dalam pengembangan kurikulum dan metode pengajaran PAI yang relevan dengan kebutuhan zaman. Studi ini menggunakan kajian pustaka dengan pendekatan konseptual serta analisis kritis terhadap literatur ilmiah, kebijakan kurikulum nasional, dan teori pembelajaran Islam. Hasil kajian menunjukkan perlunya kurikulum PAI yang inklusif dan berbasis nilai, dengan fokus pada moderasi beragama, toleransi, dan pembentukan karakter. Selain itu, metode pembelajaran perlu diarahkan pada pendekatan aktif, kolaboratif, dan aplikatif agar nilai-nilai Islam dapat diinternalisasi secara nyata dalam kehidupan siswa. Dengan demikian, pengembangan PAI perlu mengintegrasikan prinsip Islam dengan kebutuhan pendidikan modern.